Gliadin-dependent UPR induction directly triggers the expression of TG2 and pro-inflammatory cytokines, dysregulates intestinal permeability, and reduces CFTR expression in intestinal epithelial cells of celiac disease patients - Monzani, Romina; Gagliardi, Mara; Saverio, Valentina; Clemente, Nausicaa; Monzani, Alice; Rabbone, Ivana; Nigrelli, Francesca; Pellizzaro, Samuele; Ferrario, Emanuele; Saettone, Silvia; Pagano, Nico; De Leo, Luigina; et al. (Biology direct, 2025)
Celiac disease (CD) is an autoimmune disorder that primarily affects the gut of genetically predisposed individuals and is triggered by gliadin peptides (PT) produced by the digestion of gluten. Although inappropriate activation of the immune system is thought to be the main trigger of CD, the interaction between PT and intestinal epithelial cells (IECs) remains a key step. Recently, the possible involvement of ER stress in the pathogenesis of CD has been pointed out, although its role is still largely unclear. Therefore, discovering the molecular mechanism(s) activated in IECs exposed to PT represents a unique opportunity to better understand the disease and define new potential therapeutic targets. In this study we used three different experimental set-ups: intestinal biopsies from CD patients and non-CD control subjects, an in vitro model, based on human CaCo-2 cells, and an ex vivo model, based on our recently described mouse gut-ex-vivo system (GEVS), with the latter two systems were studied after stimulation with gliadin peptides (PT). To understand the signaling pathways involved we monitor the expression of a number of proteins by qPCR, Western blotting, IF, ELISA or a combination of tests. Specifically, we have analyzed the level of CD, ER stress, tissue permeability, and inflammation markers. Indeed, our study demonstrated a prompt induction of the transcription factors ATF4, ATF6 and XBP1 in IECs upon PT exposure. Thus, the upregulation of TG2 and downregulation of CFTR were prevented by ER stress inhibition/buffering by a pharmacological chaperone, also leading to restored physiological expression of OCL, CLD-2 and CLD-15, while preventing the expression of IFNγ, IL-15 and IL-17 A. Overall, our analysis has highlighted the key role of ER stress in the pathogenesis of CD and identified the chemical chaperones as a new potential valuable therapeutic treatment for CD patients.